Guru dan Kualitas Pendidikan: Sebuah Tinjauan - Bambang Widiatmoko (SIASAT, 2018)
This research aims to analyze the relationship of teacher perception about school master supervision and teacher job motivation with teacher competence of pedagogy. The unit analysis of this research is Senior Islamic High School (Madrasah Aliyah Negeri - MAN) in Bekasi City, Jawa Barat. Hypothesis testing used is regression analysis. Regression analysis method’s result show that, first: teacher perception about school master supervision and teacher competence of pedagogy has positive relationship. Second: there is positive relationship between teacher job motivation and teacher competence of pedagogy, and third: there is positive relationship between teacher perception about school master supervision and teacher job motivation with teacher competence of pedagogy in Madrasah Aliyah Negeri Bekasi.